Deletion of Seipin Attenuates Vascular Function and the Anticontractile Effect of Perivascular Adipose Tissue - Wang, Mengyu; Xing, Junhui; Liu, Mengduan; Gao, Mingming; Liu, Yangyang; Li, Xiaowei; Hu, Liang; Zhao, Xiaoyan; Liao, Jiawei; Liu, George; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2021)
Seipin is an endoplasmic reticulum (ER) membrane protein implicated in adipogenesis and lipid droplet formation. Deletion of Seipin has been well demonstrated to cause severe general lipodystrophy, however, its role in maintaining perivascular adipose tissue (PVAT) and vascular homeostasis has not been directly assessed. In the present study, we investigated the role of Seipin in mediating the anticontractile effect of PVAT and vascular function. Seipin expression in PVAT and associated vessels were detected by qPCR and western-blot. Seipin is highly expressed in PVAT, but hardly in vessels. Structural and functional alterations of PVAT and associated vessels were compared between Seipin-/- mice and WT mice. In Seipin-/- mice, aortic and mesenteric PVAT were significantly reduced in mass and adipose-derived relaxing factors (ADRFs) secretion, but increased in macrophage infiltration and ER stress, as compared with those in WT mice. Aortic and mesenteric artery rings from WT and Seipin-/- mice were mounted on a wire myograph. Vasoconstriction and vasodilation were studied in vessels with and without PVAT. WT PVAT augmented relaxation but not Seipin-/- PVAT, which suggest impaired anticontractile function in PVAT of Seipin-/- mice. Thoracic aorta and mesenteric artery from Seipin-/- mice had impaired contractility in response to phenylephrine (PHE) and relaxation to acetylcholine (Ach). In conclusion, Seipin deficiency caused abnormalities in PVAT morphology and vascular functions. Our data demonstrated for the first time that Seipin plays a critical role in maintaining PVAT function and vascular homeostasis.